2020
DOI: 10.30738/natural.v7i1.7587
|View full text |Cite
|
Sign up to set email alerts
|

Kajian profil indikator kemampuan argumentasi ilmiah pada materi zat aditif dan zat adiktif

Abstract: Argumentasi ilmiah penting untuk dikembangkan karena dapat melatih berpikir secara ilmiah, berkomunikasi, dan bertindak seperti ilmuan. Penelitian ini bertujuan untuk mengetahui kemampuan argumentasi ilmiah dan mendeskripsikan profil kemampuan argumentasi ilmiah siswa berdasarkan indikator. Penelitian melibatkan siswa kelas VIII B SMP Negeri 9 Salatiga sebagai subyek penelitian yang ditentukan melalui teknik purposive random sampling. Materi pelajaran yang dipilih adalah zat aditif dan zat adiktif. Tek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Students' conceptual understanding of the certain topic is obtained through learning activities that support the development of scientific argumentation skills [20]. This is also supported by [21] which states that when students have a good understanding of the concept, they will be able to develop good scientific argumentation skills as well. Through the understanding of the science concept, students will think logically in writing their arguments.…”
Section: Resultsmentioning
confidence: 99%
“…Students' conceptual understanding of the certain topic is obtained through learning activities that support the development of scientific argumentation skills [20]. This is also supported by [21] which states that when students have a good understanding of the concept, they will be able to develop good scientific argumentation skills as well. Through the understanding of the science concept, students will think logically in writing their arguments.…”
Section: Resultsmentioning
confidence: 99%
“…Argumentasi ilmiah juga perlu diterapkan dalam pembelajaran, karena dapat meningkatkan dan mengembanggkan pemahaman ilmiah dan dapat memperkuat pemahaman siswa (Siregar & Pakpahan, 2020). Adapun indikator argumentasi ilmiah terdiri dari; 1) claim merupakan awal dari argumentasi, dalam hal ini siswa mampu memberikan pernyataan 2) data digunakan untuk mendukung klaim, dengan adanya data dapat memperkuat pernyataan siswa 3) warrant merupakan penghubung antara pernyataan dan data atau bukti 4) rebuttal merupakan pengecualian atau penyagahan dari claim (Rahmadhani et al, 2020).…”
Section: Pendahuluanunclassified
“…The result showed that students' scientific arguments and critical thinking are low at one of the schools in Kepulauan Riau. Rahmadhani et al (2020) also researched to determine the ability of scientific argumentation and to describe the profile of students' scientific argumentation ability based on indicators. The results showed that students' scientific argumentation abilities on additive and addictive substance material for junior high school at Salatiga were included in the very good (8%), good (49%), sufficient (35%), and not good (8%) categories.…”
Section: Introductionmentioning
confidence: 99%